2019
DOI: 10.1007/s40687-019-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

PDE acceleration: a convergence rate analysis and applications to obstacle problems

Abstract: This paper provides a rigorous convergence rate and complexity analysis for a recently introduced framework, called PDE acceleration, for solving problems in the calculus of variations, and explores applications to obstacle problems. PDE acceleration grew out of a variational interpretation of momentum methods, such as Nesterov's accelerated gradient method and Polyak's heavy ball method, that views acceleration methods as equations of motion for a generalized Lagrangian action. Its application to convex varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recent studies with matrix-free methods have demonstrated the ability to solve up to 10 12 degrees of freedom with a parallel efficiency of >90 per cent (Bauer et al 2019), which is far beyond what matrix-based methods can reach. At the same time, the iterative procedure of Pseudo-transient continuation, inspired by physical processes, has been proven to solve multiphysics problems efficiently (Frankel 1950;Calder & Yezzi 2019;Räss et al 2019;Benyamin et al 2020). With matrix-free implementation, Rass et al 2019 applied a pseudo-transient solver to simulate the long-term evolution of large-scale 3-D problems (1000 3 ) and showed its ability to handle the non-linearity of Kozeny-Carman permeability and decompaction weakening.…”
Section: Numerical Methods In Geosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies with matrix-free methods have demonstrated the ability to solve up to 10 12 degrees of freedom with a parallel efficiency of >90 per cent (Bauer et al 2019), which is far beyond what matrix-based methods can reach. At the same time, the iterative procedure of Pseudo-transient continuation, inspired by physical processes, has been proven to solve multiphysics problems efficiently (Frankel 1950;Calder & Yezzi 2019;Räss et al 2019;Benyamin et al 2020). With matrix-free implementation, Rass et al 2019 applied a pseudo-transient solver to simulate the long-term evolution of large-scale 3-D problems (1000 3 ) and showed its ability to handle the non-linearity of Kozeny-Carman permeability and decompaction weakening.…”
Section: Numerical Methods In Geosciencesmentioning
confidence: 99%
“…This method is also widely known as the 2nd Richardson or relaxation method (Frankel 1950), dynamic relaxation method (Otter et al 1966;Zhang & Yu 1989) and inertial method (Poliakov et al 1993). Recently, a general framework for this type of numerical methods has been developed, known as 'PDE acceleration', which shows great potentials both for the forward and inverse modeling problems (Calder & Yezzi 2018;Benyamin et al 2020). As demonstrated by previous studies, fast PT solvers usually involve 2nd time-derivatives or 'damping factors' (Frankel 1950;Zhang & Yu 1989;Chen 2009;Benyamin et al 2020) that enable the iteration number to be linearly scaled with grid number in one direction.…”
Section: P S E U D O -T R a N S I E N T C O N T I N Uat I O N M E T H...mentioning
confidence: 99%
“…Recently, Koblitz et al [33] investigated the hydrodynamic forces for very high values of Bn. Calder and Yezzi [34] considered a rate of convergence and application for obstacle problems. In some studies mentioned therein [35][36][37][38], authors have numerically investigated the flows of incompressible non-Newtonian fluids in various computational domains.…”
Section: Outletmentioning
confidence: 99%